2022
DOI: 10.3389/fpsyg.2022.869856
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Entrepreneurship, Corporate Social Responsibilities, and Working Capital Management Practices on the Performance of Tourism Small–Medium Enterprises (SMEs) During COVID-19: Moderating Role of Employee Behavior

Abstract: The failure or success of an enterprise depends upon its working capital management practices (WCMP) along with effective corporate social responsibilities (CSR) and social entrepreneurship (SE). These factors ensure not only the soundness of financial indicators but also the profitability of an enterprise. Therefore, the objective of this study was to determine the impact of CSR, SE, and WCMP on the performance of small–medium enterprises (SMEs) of tourism sector, during the lockdown period in Malaysia. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…According to Stoian and Gilman (2017), CSR activities in SMEs can enhance the growth of a firm. This result is in line with previous studies and with management literature that affirms the positive relationship between CSR and firm performance (Luo and Homburg 2007;Maignan et al 1999;Qu 2009) and the positive association between CSR and SME per-formance (Ionescu 2021;Li et al 2022;Tsoutsoura 2004;Waddock and Graves 1997). It has been also shown that the relationship between CSR and sustainable financial performance is positive when moderated by entrepreneurship (Luo et al 2022).…”
Section: Philanthropic Csrsupporting
confidence: 92%
See 2 more Smart Citations
“…According to Stoian and Gilman (2017), CSR activities in SMEs can enhance the growth of a firm. This result is in line with previous studies and with management literature that affirms the positive relationship between CSR and firm performance (Luo and Homburg 2007;Maignan et al 1999;Qu 2009) and the positive association between CSR and SME per-formance (Ionescu 2021;Li et al 2022;Tsoutsoura 2004;Waddock and Graves 1997). It has been also shown that the relationship between CSR and sustainable financial performance is positive when moderated by entrepreneurship (Luo et al 2022).…”
Section: Philanthropic Csrsupporting
confidence: 92%
“…ESE and SESE are two dependent variables that are dominant predictors for performance (Bandura 1977(Bandura , 1982(Bandura , 1986Bandura and Schunk 1981). In this study, potential mediators were organizational capabilities and philanthropic CSR, as they are both a source of competitive advantage (Collis 1994;Ionescu 2021;Li et al 2022;Teece et al 1997;Waddock and Graves 1997), and hence, they could play an important role in influencing the performance of sustainable entrepreneurs.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Important variances among businesses indicate a failure to adjust financial measures that decide entrepreneurship healthiness. Thus, the impact of social obligations and working capital management practices on the presentation of tourism SMEs during covid-19 were discussed in the research proposed by [12].…”
Section: Related Workmentioning
confidence: 99%